2018
DOI: 10.1186/s12943-018-0771-7
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circ-ITCH inhibits bladder cancer progression by sponging miR-17/miR-224 and regulating p21, PTEN expression

Abstract: BackgroundCirc-ITCH is a circRNA generated from several exons of itchy E3 ubiquitin protein ligase (ITCH) and tumor suppressor served as a sponge for certain miRNAs targeting their parental transcripts of ITCH. However, the role of circ-ITCH in bladder cancer (BCa) was not reported. In the present study, we investigated the role of circ-ITCH in BCa.MethodsQuantitative real-time PCR was used to detect the expression of circ-ITCH and survival analysis was adopted to explore the association between circ-ITCH expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
357
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 414 publications
(366 citation statements)
references
References 34 publications
9
357
0
Order By: Relevance
“…At present, increasing studies demonstrate that circRNAs take part in complicated physiological and pathological processes, and serve as miRNA sponges to regulate related target genes (Hansen, Kjems, & Damgaard, ; X. Meng et al, ). Bladder cancer could be inhibited by circ‐ITCH via sponging miR‐17/miR‐224 (Yang et al, ). HSCR, a congenital intestinal disease, is caused by defects in the migration of ENCCs.…”
Section: Discussionmentioning
confidence: 99%
“…At present, increasing studies demonstrate that circRNAs take part in complicated physiological and pathological processes, and serve as miRNA sponges to regulate related target genes (Hansen, Kjems, & Damgaard, ; X. Meng et al, ). Bladder cancer could be inhibited by circ‐ITCH via sponging miR‐17/miR‐224 (Yang et al, ). HSCR, a congenital intestinal disease, is caused by defects in the migration of ENCCs.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that circRNAs could act as miRNA sponges that regulate gene expression. 23 To determine whether circMTO1 interacts with miRNAs, RIP experiment was performed. Results of RIP showed that circMTO1 was significantly enhanced in the Ago2 group in comparison with the control ( Figure 5A).…”
Section: Circmto1 Is a Target Of Mir-17-5pmentioning
confidence: 99%
“…Due to the application of next‐generation sequencing and bioinformatics, circRNAs were now discovered to be widely expressed in cells, exceeding the abundance of the linear mRNAs . circRNAs have now become a new star in RNA research field, as recent reports revealed their critical roles in various biological processes . They can mediate gene expression by sponging miRNAs and RBPs as well as regulating transcription and alternative splicing.…”
Section: Discussionmentioning
confidence: 99%
“…5,10,20 circRNAs have now become a new star in RNA research field, as recent reports revealed their critical roles in various biological processes. 12,[21][22][23][24] They can mediate gene expression by sponging miRNAs and RBPs as well as regulating transcription and alternative splicing. Notably, recent evidence also shows that some circRNAs can be translated into proteins, 25,26 which expands the definition and function of circRNA.…”
Section: Potential Diagnostic Value Of Hsa_circ_0137287 In Ptcmentioning
confidence: 99%